Authenticity in leadership: Reframing relational transparency through the lens of emotional labour. (June 2019) - Kempster, Steve; Iszatt-White, Marian; Brown, Matt
In this paper we problematise relational transparency as an element of authentic leadership when viewed through the lens of emotional labour. Using the method of analytic co-constructed auto-ethnography we examine a senior hospital manager's experience of seeking to be authentic during a period of intense challenge as he pursues the closure of a hospital ward. A first-person account is developed that speaks to the necessity of hiding felt emotions and displaying his perceptions of desired emotions warranted in the context in which he seeks to lead. That this is not experienced as inauthentic is seen as deriving from two dimensions of experienced authenticity: strength of identification with leadership role and fidelity to leadership purpose. The veracity of this reframing of authenticity in leadership practice is explored through a second study, of practising leaders required to balance the demands of performing emotional labour and appearing and feeling authentic. We suggest that reframing relational transparency as 'fidelity to purpose' may be a valuable counterweight to the goal of relational transparency promulgated by the leadership industry and a practical advance for those seeking to practise authentic leadership.